Bacteria as Precision Tools for Cancer Therapy - Carmen Michán; José Prados; Juan‐Luis Ramos (Microbial Biotechnology)
ABSTRACT The discovery at the end of the 20th century of genes that induce cell death revolutionised the biocontaintment of genetically manipulated bacteria for environmental or agricultural applications. These bacterial ‘killer’ genes were then assayed for their potential to target and control malignant cells in human cancers. The identification of the bacteriomes in different human organs and tissues, coupled with the observation that bacteria tend to accumulate near tumours, has opened new avenues for anti‐cancer strategies. This progress, along with recent insights into how cancer cells evade immune response, has prompted innovative therapeutic approaches. Tumour microenvironments are typically nutrient‐rich, characterised by low oxygen tensions and very resistant to immune responses. Two recent studies in MBT highlight the promise of using Salmonella typhimurium and Escherichia coli as vectors in novel cancer treatments. Engineered S. typhimurium strains can generate adjuvant flagellin‐antigen complexes that function as in situ vaccines, hence increasing the immunogenic responses within tumour environment. Similarly, gut E. coli can be used as vectors to targert tumour cells in colon cancer, enabling both diagnostic applications and localised treatments. Both approaches hold significant potential to improve patient survival outcomes.